Transcriptome profiling of macrophages persistently infected with human respiratory syncytial virus and effect of recombinant Taenia solium calreticulin on immune-related genes - Rivera-Toledo, Evelyn; Fernández-Rojas, Miguel A.; Santiago-Olivares, Carlos; Cruz-Rivera, Mayra; Hernández-Bautista, Vania; Ávila-Horta, Fernanda; Flisser, Ana; Mendlovic, Fela (Frontiers in Microbiology, 2024)
Human respiratory syncytial virus (hRSV) is a main cause of bronchiolitis in infants and its persistence has been described in immunocompromised subjects. Using a comprehensive microarray approach, we analyzed the transcriptome profile of a macrophage cell line that has supported hRSV persistence for over 150 passages. We compared the gene expression of persistently infected and non-infected macrophages. We also evaluated the effect of a recombinant Taenia solium-derived calreticulin (rTsCRT) on hRSV-infected macrophage gene transcription, as well as on cytokine production and number of copies of the persistent hRSV genome. Our results showed that hRSV long-term virus infection significantly alters mRNA expression of antiviral, inflammatory, as well as arginine and lipid metabolismassociated genes, revealing a transcriptional signature that suggests a mixed M1/M2 phenotype. The resulting host-virus equilibrium allows for the regulation of viral replication while evading the antiviral and proinflammatory responses. Interestingly, rTsCRT stimulus upregulated Tnfα, Il6 and Nos2 mRNA. We found increased levels of both proinflammatory cytokines and nitrite levels in the conditioned media of persistent macrophages treated with rTsCRT. This increase was associated with a significant reduction in viral genome copies. We conclude that hRSV persistently infected macrophages retain responsiveness to external stimuli and demonstrate that the profound changes induced by viral persistence are potentially reversible. Our observations contribute to the understanding of the mechanisms related to hRSV persistence in macrophages and have implications for the development of targeted therapies to eliminate persistent infections or reduce the negative effects related with chronic inflammatory diseases associated with hRSV infection.